Three inequalities for quadratic-phase Fourier transform - Bahri, Mawardi (Hilbert Journal of Mathematical Analysis, 2023)
In this work, we introduce the one-dimensional quadratic-phase Fourier transform. The relation between one-dimensional quadratic-phase Fourier transform and one-dimensional Fourier transform is discussed in detail. We finally propose several versions of the inequalites related to one-dimensional quadratic-phase Fourier transform.